The Effects of Interdisciplinary Bedside Rounds on Patient Centeredness, Quality of Care, and Team Collaboration: A Systematic Review. Issue 1 (January 2022) - Heip, Tine; Van Hecke, Ann; Malfait, Simon; Van Biesen, Wim; Eeckloo, Kristof
Abstract : Background: Research indicates that having multiple healthcare professions and disciplines simultaneously at the patient's bedside improves interprofessional communication and collaboration, coordination of care, and patient-centered shared decision-making. So far, no review has been conducted, which included qualitative studies, explores the feasibility of the method, and looks at differences in definitions. Objectives: The aim of the study was to explore available evidence on the effects of interdisciplinary bedside rounds (IBRs) on patient centeredness, quality of care and team collaboration; the feasibility of IBRs; and the differences in definitions. Data Sources: PubMed, Web of Science, and Cochrane databases were systematically searched. The reference lists of included articles and gray literature were also screened. Articles in English, Dutch, and French were included. There were no exclusion criteria for publication age or study design. Study Appraisal and Synthesis Methods: The included (N = 33) articles were critically reviewed and assessed with the Downs and Black checklist. The selection and summarizing of the articles were performed in a 3-step procedure, in which each step was performed by 2 researchers separately with researcher triangulation afterward. Conclusions and Implications of Key Findings: Interdisciplinary bedside round has potentially a positive influence on patient centeredness, quality of care, and team collaboration, but because of a substantial variability in definitions, design, outcomes, reporting, and a low quality of evidence, definitive results stay uncertain. Perceived barriers to use IBR are time constraints, lack of shared goals, varied responsibilities of different providers, hierarchy, and coordination challenges. Future research should primarily focus on conceptualizing IBRs, in specific the involvement of patients, before more empiric, multicentered, and longitudinal research is conducted. Abstract : Supplemental digital content is available in the text.